2009
DOI: 10.1105/tpc.108.063552
|View full text |Cite
|
Sign up to set email alerts
|

A 1-Megadalton Translocation Complex Containing Tic20 and Tic21 Mediates Chloroplast Protein Import at the Inner Envelope Membrane

Abstract: Chloroplast protein import is mediated by two hetero-oligomeric protein complexes, the Tic and Toc translocons, which are located in the inner and outer envelope membranes. At the inner membrane, many Tic components have been identified and characterized, but it remains unclear how these Tic proteins are organized to form a protein-conducting channel or whether a stable Tic core complex that binds translocating preproteins exists. Here, we report the identification of a 1-megadalton (MD) translocation complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 65 publications
8
131
0
Order By: Relevance
“…We found this TIC complex to be absolutely required for photosynthetic protein import in green tissues and, thus, essential for plant viability in Arabidopsis (Hirabayashi et al, 2011;Kikuchi et al, 2013). Experimental evidence for the presence of a similar TIC complex in pea (Pisum sativum) (Kikuchi et al, 2009) supports the idea that this complex is a general feature of the TIC apparatus. The TIC complex and Ycf1 appear to have evolved dramatically along with the evolution of the green lineage, including green algae and land plants; thus, they can be regarded as a "general green TIC.…”
supporting
confidence: 59%
“…We found this TIC complex to be absolutely required for photosynthetic protein import in green tissues and, thus, essential for plant viability in Arabidopsis (Hirabayashi et al, 2011;Kikuchi et al, 2013). Experimental evidence for the presence of a similar TIC complex in pea (Pisum sativum) (Kikuchi et al, 2009) supports the idea that this complex is a general feature of the TIC apparatus. The TIC complex and Ycf1 appear to have evolved dramatically along with the evolution of the green lineage, including green algae and land plants; thus, they can be regarded as a "general green TIC.…”
supporting
confidence: 59%
“…1A). Unlike atTic40, mature SSU is a soluble stromal protein, and previous studies have defined specific intermediates at several stages of import through the TOC-TIC complexes in in vitro import reactions (13,(21)(22)(23)(24)(25). Import intermediates for both preproteins coprecipitated Hsp90C as well as Tic110 and Toc75 (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…We cannot exclude the possibility that the region not covered by our analyses, the TM3 and TM4 regions of model 1, provided the channel activity observed in the reconstituted liposome. Of note is the fact that the six-transmembrane-domain topology of Tic110 was deduced using isolated inner membrane vesicles (Balsera et al, 2009), while experiments using intact chloroplasts have shown that the region after TM2 is entirely inside the stroma (Kessler and Blobel, 1996;Jackson et al, 1998;Chou et al, 2003;Inaba et al, 2003Inaba et al, , 2005Kikuchi et al, 2009). Isolated inner membrane vesicles may have mixed orientations and may complicate the experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the higher than calculated molecular mass was due to a possible non-globular shape of Tic110 (Balsera et al, 2009). Pea and Arabidopsis Tic110 also migrated as dimers on blue native (BN)-PAGE when solubilized from chloroplast membranes (Kikuchi et al, 2009(Kikuchi et al, , 2013. The calculated molecular masses of CmTic110 B and CmTic110 C are 59.9 and 42.8 kDa, respectively.…”
Section: Crystal Structure Of Cmtic110 Cmentioning
confidence: 97%
See 1 more Smart Citation